2001
DOI: 10.1377/hlthaff.20.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences With Hospital Care In Five Countries

Abstract: Analysis of patient surveys carried out in Germany, Sweden, Switzerland, the United Kingdom, and the United States in 1998-2000 revealed high rates of problems during inpatient hospital stays. Problems with information and education, coordination of care, respect for patients' preferences, emotional support, physical comfort, involvement of family and friends, and continuity and transition were prevalent in all five countries. These dimensions of patients' experience appear to be salient and relevant in each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
0
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 7 publications
3
126
0
10
Order By: Relevance
“…In Germany, Sweden, Switzerland and Great Britain, a literature review indicated percentages of dissatisfied patients respectively of 6.6%, 7.4% 3.7% 8.5% in studies conducted between 1998 and 2000 [22].. Results of numerous studies conducted in hospital services in different countries support this tendency.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In Germany, Sweden, Switzerland and Great Britain, a literature review indicated percentages of dissatisfied patients respectively of 6.6%, 7.4% 3.7% 8.5% in studies conducted between 1998 and 2000 [22].. Results of numerous studies conducted in hospital services in different countries support this tendency.…”
Section: Discussionmentioning
confidence: 93%
“…For 17.2% of Germans, 13.3% of Swiss, 21.9% of Britishs and 21.7% of Americans coordination of care services is perceived as a key problem in their respective countries [22]. In a recent American survey of 2268 women suffering from breast cancer, 16.4% consider the coordination of care to be inadequate [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International research indicates that continuity and transition is the most problematic dimension of patient care across five countries where patient experience surveys have been conducted. 23 Several state health departments have also recognised the need for improvements in discharge processes and have developed improvement frameworks to address this issue. 24,25 Detailed discharge planning is essential for continuity of care for people with ongoing care needs, providing a link between treatments received in hospital and post-discharge care provided in the community.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes disheartening as the death rate in most developing countries increases even due to minor ailments that could have being treated [2].…”
Section: Introductionmentioning
confidence: 99%